Evaluation of Essential Fatty Acids in Lactating Sow Diets on Sow Reproductive Performance, Colostrum and Milk Composition, and Piglet Survivability - Julia P. Holen; Jason C. Woodworth; Mike D. Tokach; Robert D. Goodband; Joel M. DeRouchey; Jordan T. Gebhardt; Ashley E. DeDecker; Xochitl Martinez (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 3,451 mixed parity sows and their litters were used to evaluate the effects of essential fatty acid intake on sow reproductive performance, piglet growth and survivability, and colostrum and milk composition. At approximately d 112 of gestation, sows were blocked by parity within farrowing room and randomly assigned to 1 of 4 experimental treatments. Lactation diets were corn-soybean meal-wheat-based and included 0.5 (Control) or 3% choice white grease (CWG), 3% soybean oil (SO), or a combination of 3% soybean oil and 2% choice white grease (Combination). Thus, sows were provided diets with low essential fatty acid (EFA; as linoleic [LA] and α-linolenic acid [ALA]) in diets with choice white grease or high EFA in diets with soybean oil. Prior to farrowing, sows were provided 4 lb/d of their assigned lactation diet and then allowedad libitumaccess after parturition. Overall lactation ADFI increased (P<0.001) when sows were fed the Combination and CWG treatments compared to sows fed the Control or diet with 3% SO. Regardless of differences among ADFI, daily LA and ALA intake of sows assigned to the Combination and SO treatments were greater (P<0.001) than sows fed diets with lower EFA provided as CWG. There was no effect of sow EFA intake on piglet survivability from birth to 24 h or from 24 h to weaning (P>0.10). Overall, sows consuming high EFA provided in the Combination and SO diets produced litters with greater (P<0.05) litter gain and litter ADG during the lactation period and heavier (P<0.001) piglet weaning weights when compared to litters from sows fed diets with low EFA provided through CWG. Lactation diet EFA composition did not influence colostrum or milk dry matter, crude protein, or crude fat content (P>0.10). However, LA and ALA content in both colostrum and milk at weaning increased (P<0.05) in response to increased EFA levels in diets that contained SO. There was no evidence for differences (P>0.10) in wean-to-estrus interval, percentage of sows bred by d 7, percentage of sows bred by d 12, farrowing rate, or subsequent farrowing performance due to sow lactation EFA intake. In conclusion, increased LA and ALA intake during the lactation period from soybean oil addition increased overall litter growth and average weaning weights of pigs but did not affect piglet survivability or subsequent reproductive performance of sows.
Keywords: alpha-linolenic acid; essential fatty acids; lactation; linoleic acid; sows